Transitions from lower track secondary schools into vocational training: Does a detour pay off? - Annette Hillerich-Sigg (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
This paper analyzes the effect of alternative transition paths after grade 9 of German lower secondary school on vocational training. Using a selection-on-observables approach I show that a delayed transition into vocational training after lower track secondary school is not a disadvantage conditional on a successful transition into vocational training. Students benefit from continuing general schooling or attending vocational school compared to transitioning directly with regard to wages paid during vocational training as well as average wages, prestige, and socioeconomic status of the training occupation. This comes at the cost of a lower probability to match the training occupation with the reported desired occupation and being less satisfied with the vocational training. Participation in pre-vocational training does not lead to a different type of vocational training position than after a direct transition. However, those participants are less satisfied with their vocational training.
Keywords: J24; I28; I26; 330; school-to-work transition; secondary school; pre-vocational training; vocational training